2021
DOI: 10.1177/01461672211007228
|View full text |Cite
|
Sign up to set email alerts
|

Low Self-Control: A Hidden Cause of Loneliness?

Abstract: Loneliness has been associated with multiple negative outcomes. But what contributes to loneliness in the first place? Drawing from the literature on the importance of self-regulatory ability for successful social functioning, the present research explored the role of low self-control as a factor leading to loneliness. A set of four studies (and three additional studies in Supplementary Online Materials ) using cross-sectional, experimental, daily diary, and experience sampling methods showed that lower self-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 66 publications
2
28
0
1
Order By: Relevance
“…But later investigations have also focused on the negative outcomes of poor self-control development among youth, for example, as a function of adverse childhood experiences and its implications on familial relationships ( Jones et al, 2021 ; Tehrani & Yamini, 2020 ). Studies show that lower self-control is potentially damaging not only for existing relationships as showing less forgiveness and hit back intentions ( Burnette et al, 2014 ) but it also acts as a wall against forming new relationships ( Stavrova, et al, 2022 ). Jones et al (2021) also found that youth had more self-control when they shared close familial ties and parental monitoring had a potent positive effect on their self-control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But later investigations have also focused on the negative outcomes of poor self-control development among youth, for example, as a function of adverse childhood experiences and its implications on familial relationships ( Jones et al, 2021 ; Tehrani & Yamini, 2020 ). Studies show that lower self-control is potentially damaging not only for existing relationships as showing less forgiveness and hit back intentions ( Burnette et al, 2014 ) but it also acts as a wall against forming new relationships ( Stavrova, et al, 2022 ). Jones et al (2021) also found that youth had more self-control when they shared close familial ties and parental monitoring had a potent positive effect on their self-control.…”
Section: Discussionmentioning
confidence: 99%
“…Research also explored the relationship between self-control and loneliness and found a negative association between them ( Hamama et al, 2000 ; McWhirter, 1997 ; Özdemir et al, 2014 ). Self-control has been associated with good interpersonal relationships as restraining one’s yearnings, urges, and impulses will lead to better social relationships and lower the probability of ostracism and subsequently loneliness ( Stavrova et al, 2022 ). This association reflects that people with high self-control generally do not feel lonely, or again, people high on loneliness cannot have good self-control.…”
Section: Self and Lonelinessmentioning
confidence: 99%
“…We contribute to this work by investigating a certain incident of ostracism (i.e., rejection with an unclear reason in a performance context) and focusing on anticipated devaluation and support. This line of work suggests that under certain conditions the individuals can devalue and further reject the target when, for example, they think the target is burdensome (e.g., Wesselmann et al., 2013) or have certain unattractive dispositions (e.g., Ren & Evans, 2020; Rudert et al., 2020; Stavrova et al., 2021) or when they think the sources had a punitive motive (e.g., Rudert et al., 2018). We extend this line of work by showing that in the context of rejection in a work context—targets see disclosing a rejection experience as more costly than disclosing an instance where they were removed from the group randomly.…”
Section: Discussionmentioning
confidence: 99%
“…However, when employees resolve cyberloafing to cope with a specific 3 kind of negative emotion, such as workplace loneliness, it could be maladaptive because cyberloafing seems to be harmful for employees to reconnect with other coworkers (Tandon et al, 2021). Studies in psychology also suggest that loneliness may cause the loss of self-control resources (Baumeister et al, 2005;Stavrova et al, 2022) and lead to problematic addictive behaviors (e.g., gambling, Sirola et al, 2019; internet addiction, Bian and Leung, 2015). Despite such evidence, unfortunately, whether and how workplace loneliness may lead to cyberloafing and measures to mitigate the effects remain underexplored in the extant internet research literature.…”
Section: Introductionmentioning
confidence: 99%